2021
DOI: 10.31235/osf.io/p5sfd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

More than a COVID-19 response: Sustaining mutual aid groups during and beyond the pandemic

Abstract: Mutual aid groups have been an indispensable part of the public response to the COVID-19 pandemic. They have provided many forms of support, in particular grocery shopping which has enabled people to self-isolate if required. While community solidarity during emergencies and disasters is common, previous studies have shown that such solidarity behaviours tend to decline over time, even when needs remain high. In this study, we address how mutual aid groups can be sustained over time in the context of the COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…5. Provide practical support and resources to ensure the sustainability of Mutual Aid groups, which provide multiple forms of practical support to those in the community, from delivering food, providing emotional support, to walking the dog (Fernandes‐Jesus et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5. Provide practical support and resources to ensure the sustainability of Mutual Aid groups, which provide multiple forms of practical support to those in the community, from delivering food, providing emotional support, to walking the dog (Fernandes‐Jesus et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is very difficult for such groups to sustain themselves over an extended period of time. The Government can play an important part in scaffolding such self‐organization by, for instance, providing resources and providing payment for volunteers (Fernandes‐Jesus et al., 2021 ). There are successful examples of this in the UK’s Ministry of Housing, Communities and Local Government (MHCLG) Community Champions scheme that has operated through two mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, one can say that community‐based support arose during the COVID‐19 pandemic, and volunteers were one of the main actors who took the responsibility of helping. Recent research has shown that mutual aid groups were very productive during the COVID‐19 pandemic in terms of meeting community needs more strategically and systematically (Fernandes‐Jesus et al., 2021 ; Stansfeld et al., 2020 ). However, we also found that individual volunteers can also take steps to help their community members when there is an emergency.…”
Section: Discussionmentioning
confidence: 99%
“…Subcategory 1-organizations/associations/faith communities Because local and social healthcare services were overwhelmed throughout the pandemic, not all community members could be supported by those services (Stevenson et al, 2020). Therefore, COVID-19 mutual-aid groups (Fernandes-Jesus et al, 2021), neighborhood associations, and community support groups arose to meet the needs of their community members. As the members and volunteers of community aid and support groups are mainly the community members, they are already familiar with the needs and the strengths of their own community, and it is easier for these groups (including faith communities) to assist their community members and neighbors.…”
Section: Main Category 3: Who Is the Supporter(s)?mentioning
confidence: 99%
See 1 more Smart Citation